GERAKAN SOSIAL WARGA PARANGKUSUMO PADA KASUS PENGGUSURAN LAHAN GEO MARITIM PARK - Ahmad Izudin; Suyanto Suyanto (Jurnal Sosiologi Reflektif, 2019)
This paper aims to describe about unravel the tangled thread of the case of the eviction of Parang Kusumo residents in Bantul Regency, Yogyakarta. The central point outlined in this study is to explain the dynamics of social movements of people affected by evictions due to the Geo Maritim Park development plan. Analysis obtained from observations of field data through indept-interview with purposive sampling method shows that the case of the resistance movement of people affected by eviction experienced a ‘defeat’ in the public space. The defeat was identified because the strength of legal legality (land certificates) owned by residents was not strong and some even refused demonstrations initiated by the People’s Alliance to Refuse Eviction (Aliansi Rakyat Menolak Penggusuran—ARMP). As a case in the vortex of conflict, the people’s struggle to seize their rights was captured by elitist interests in the Sultan’s ground and the Pakualaman’s ground.Artikel ini hendak mengurai benang kusut kasus penggusuran warga Parang Kusumo Kabupaten Bantul Yogyakarta. Menjadi titik sentral yang diuraikan dalam kajian ini adalah menjelaskan dinamika gerakan sosial warga yang terkena dampak penggusuran akibat rencana pembangunan Geo Maritim Park. Analisa yang di dapat dari hasil pengamatan data lapangan melalui indept-interview dengan metode purposive sampling memperlihatkan bahwa kasus gerakan perlawanan warga terkena dampak penggusuran mengalami ‘kekalahan’ di ruang publik. Kekalahan tersebut teridentifikasi karena kekuatan legalitas hukum (sertifikat tanah) yang dimiliki warga tidak kuat bahkan sebagian menolak aksi demonstrasi yang diinisiasi oleh Aliansi Rakyat Menolak Penggusuran (ARMP). Sebagai kasus yang berada dalam pusaran konflik, perjuangan warga untuk merebut hak-hak mereka tersandra oleh kepentingan elitis dalam bingkai sultan ground dan pakualaman ground.